2016
DOI: 10.1002/jcp.25425
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Estrogen Receptor α and β Levels and Activation Status in LPS‐Stimulated Human Macrophages

Abstract: Immune function, inflammation, and atherosclerosis display sex differences and are influenced by 17β-estradiol through estrogen receptors subtypes ERα and ERβ. Male tissues express active ERs, but their possible involvement in inflammation in males has never been assessed. Macrophages express both ERα and ERβ and offer the opportunity to evaluate the role of ER levels and activation in inflammation. We assessed the ability of lipopolysaccharide (LPS) to modulate, in a sex-specific way, the expression and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
1
25
1
Order By: Relevance
“…Epidemiological studies have highlighted the association of AAA with risk factors including age, male sex, smoking, hypertension or low HDL-cholesterol levels 1 . Interestingly, these factors may impact on monocyte/ macrophage activity and function 37,[163][164][165][166][167][168] . Additional research will be required to explore the molecular pathways that could link those risk factors with the contribution of monocytes/macrophages to AAA.…”
Section: Monocytes and Macrophages As Therapeutic Targets In Aaamentioning
confidence: 99%
“…Epidemiological studies have highlighted the association of AAA with risk factors including age, male sex, smoking, hypertension or low HDL-cholesterol levels 1 . Interestingly, these factors may impact on monocyte/ macrophage activity and function 37,[163][164][165][166][167][168] . Additional research will be required to explore the molecular pathways that could link those risk factors with the contribution of monocytes/macrophages to AAA.…”
Section: Monocytes and Macrophages As Therapeutic Targets In Aaamentioning
confidence: 99%
“…Studies about ERβ and macrophage function are limited; Kramer and colleagues [ 107 ] showed that ERβ suppresses CD16 expression with no effect on the activation of MAPKs and NF-κB, while Xing et al [ 94 ] demonstrated an opposite effect showing the ability of selective ERβ activation to inhibit expression of inflammatory mediators. A recent study in human macrophages demonstrated that LPS is able to increase ERα phosphorylation but has no effect on ERβ activation [ 108 ]. This study also showed that macrophages isolated from males are more sensitive to the LPS effects than those from females.…”
Section: Estrogen Receptors In the Monocyte/macrophage Systemmentioning
confidence: 99%
“…This was determined by measuring the removal of 3 H-cholesterol from macrophages to the liver, and subsequently to feces. Interestingly, Campesi et al reported that the presence of lipopolysaccharides, which are known to increase the morbidity and mortality of atherosclerotic diseases, give rise to a sex-specific difference in human blood-monocytes derived macrophage ERα activation, with males showing a significantly higher level of expression than females [ 63 ].…”
Section: Role Of Estrogen Receptors In Vascular Pathologymentioning
confidence: 99%
“…Though the mechanisms by which ERα protects against the development of atherosclerosis are widely studied, the role of ERβ remain less thoroughly investigated and controversial [ 63 , 70 ]. Similar to ERα, ERβ is known to be expressed in both endothelial and VSMC of arteries [ 70 , 71 ].…”
Section: Role Of Estrogen Receptors In Vascular Pathologymentioning
confidence: 99%